Politik Hukum Kedudukan Wakil Presiden dalam Badan Pengarah Percepatan Pembangunan Otonomi Khusus Papua - Pasalli, Maleakhi Samuel; Nurafifah, Yamuna; Gunawan, Pranaldo (UI Scholars Hub, 2025)
The legal policy regarding the amendment of Law Number 21 of 2001 into Law Number 2 of 2021 concerning Special Autonomy for Papua marks a paradigm shift from asymmetric decentralization towards controlled autonomy or leading to the centralization of power, notably through the establishment of the Steering Committee for Acceleration of Development of Special Autonomy for Papua (BP3OKP), which is chaired directly by the Vice President. This research is motivated by juridical issues wherein the Academic Paper (Naskah Akademik) of the amendment fails to provide scientific justification regarding the urgency of establishing this special body or the involvement of the Vice President, as well as the potential distortion of the constitutional aspects of the Vice President's position within the presidential system. The primary objective of this study is to analyze the legal policy behind the formation of BP3OKP and to examine the constitutionality of the Vice President's position as the chair of said body, having obtained authority through attribution. The findings indicate that Article 68A, which regulates BP3OKP, emerged from a top-down and elitist political process lacking a scientific basis in the Academic Paper, reflecting an authoritarian political configuration that yields an orthodox legal product in the interest of recentralizing central power. Furthermore, the designation of the Vice President as the Chair of BP3OKP through statutory attribution is deemed unconstitutional as it obscures the Vice President’s position, which, under the 1945 Constitution, should strictly be that of an assistant to the President with delegated, rather than attributive, authority. This study concludes that the institutional design of BP3OKP constitutes a form of political design that places the Vice President outside the domain of a pure presidential system, thereby resulting in overlapping local governance and the implementation of Papua's special autonomy.